PENGEMBANGAN MEDIA PEMBELAJARAN PKN SD BERBASIS POWTOON UNTUK MENGEMBANGKAN KARAKTER TANGGUNG JAWAB SISWA KELAS IV - Edy Wasono; Sutrisna Wibawa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The research conducted focused on the development of video learning media based on Powtoon for the content of Civics Education for grade IV elementary schools, especially the material on rights and obligations in theme 2: Always Saving Energy. The implementation of this research used the R&D development research method with the ADDIE model. In the ADDIE model there are five stages, namely Analyze, Design, Develop, Implement, and Evaluate. However, in this study, the researchers only conducted to the point of Develop because this study aimed to develop appropriate learning media based on the assessment of the validator. The results of the validation of learning media by media experts, material experts, and linguists obtained a score of 84% which was included in the very eligible or very good category because the percentage of validation results was in the range of 81-100%. Thus, based on video learning media Powtoon for Civics was very feasible to be used for the learning process. Based on video learning media Powtoon can increase the use of technology, and it also makes students enthusiastic in participating in the learning process.